The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000449470
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning Immune and Endocrine Parameters in Humans: A Systematic Review

Abstract: The final selection included 16 studies. Overall, those studies indicate that conditioning of immunosuppression, conditioning of allergic responses, and conditioning of insulin and glycemic responses is possible. Regarding immunostimulants, antiallergic effects, and cortisol conditioning, the preliminary results are promising, but additional studies are needed. Conclusions: This systematic review shows classical conditioning of immune and endocrine responses for various pharmaceutical substances. The studies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…If this combination of factors leads to a positive expectancy, it will likely result in a beneficial or improved outcome through the placebo effect, whereas negative expectancies could induce harmful outcomes due to the activation of the nocebo effect. Overall, we can state that these phenomena are associated to cognitive–affective factors that can trigger a top-down neural and biochemical modulation of different physiological processes, thus influencing pain (Benedetti, Pollo, & Colloca, 2007; Colloca & Grillon, 2014; Petersen et al, 2014; Price, Craggs, Nicholas Verne, Perlstein, & Robinson, 2007), fatigue (Shaibani, Frisaldi, & Benedetti, 2017), Parkinson’s disease (Frisaldi et al, 2017; Udupa & Fox, 2015), immunity (Tekampe et al, 2017; Wendt, Albring, & Schedlowski, 2014), irritable bowel syndrome (Ballou et al, 2017; Kaptchuk et al, 2010), and the effectiveness of medications (Ader et al, 2010; Bingel et al, 2011; Colloca, Enck, & DeGrazia, 2016), among others. While ethical considerations have always been of concern due to an association of the effectiveness of placebos with deception, newer research has found that placebo effects can occur even when an individual is aware of receiving or having received a placebo intervention (Ballou et al, 2017; Carvalho et al, 2016; Colloca, Pine, Ernst, Miller, & Grillon, 2016; Kaptchuk et al, 2010; Locher et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…If this combination of factors leads to a positive expectancy, it will likely result in a beneficial or improved outcome through the placebo effect, whereas negative expectancies could induce harmful outcomes due to the activation of the nocebo effect. Overall, we can state that these phenomena are associated to cognitive–affective factors that can trigger a top-down neural and biochemical modulation of different physiological processes, thus influencing pain (Benedetti, Pollo, & Colloca, 2007; Colloca & Grillon, 2014; Petersen et al, 2014; Price, Craggs, Nicholas Verne, Perlstein, & Robinson, 2007), fatigue (Shaibani, Frisaldi, & Benedetti, 2017), Parkinson’s disease (Frisaldi et al, 2017; Udupa & Fox, 2015), immunity (Tekampe et al, 2017; Wendt, Albring, & Schedlowski, 2014), irritable bowel syndrome (Ballou et al, 2017; Kaptchuk et al, 2010), and the effectiveness of medications (Ader et al, 2010; Bingel et al, 2011; Colloca, Enck, & DeGrazia, 2016), among others. While ethical considerations have always been of concern due to an association of the effectiveness of placebos with deception, newer research has found that placebo effects can occur even when an individual is aware of receiving or having received a placebo intervention (Ballou et al, 2017; Carvalho et al, 2016; Colloca, Pine, Ernst, Miller, & Grillon, 2016; Kaptchuk et al, 2010; Locher et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Resultantly, only being in the hospital can evoke these symptoms (Stockhorst, Enck, & Klosterhalfen, 2007). Together with studies on conditioned antiallergic effects, reviewed earlier, these findings show that, despite the relatively small conditioned effects found in laboratory studies (Ader, 2003;Tekampe, van Middendorp, Meeuwis, et al, 2017), conditioned pharmacological responses can elicit clinically relevant symptoms. Further studies in patient samples will be needed to unravel the full potential of pharmacological conditioning in eliciting clinically relevant changes in symptoms.…”
Section: Opportunities For Research and Clinical Practicementioning
confidence: 60%
“…These mechanisms seem to differ between UCSs (Schedlowski & Pacheco-Lopez, 2010). Potentially these underlying mechanisms also differ depending on the population targeted, with on the one hand allergic patients who are familiar with the UCS as well as UCR and on the other hand healthy volunteers for whom UCS as well as UCR is unfamiliar prior to the study (Tekampe, van Middendorp, Meeuwis, et al, 2017). More research into the underlying mechanisms by which conditioning takes place in different populations may provide insight into the design characteristics that make for successful conditioning and hence point to opportunities for effectively bringing conditioned pharmacological responses into clinical practice.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is known that mechanical stimulation of the skin during scratching leads to a release of proinflammatory cytokines which in turn worsen itch. Moreover, placebo research on expectancies has shown that immune and endocrine reactions can be learned by conditioning and evoked without pharmacologically active substances . Attention, negative affect and expectancies also influence the behavioural component of itch, such as scratching behaviour and limited medication adherence in chronic skin disease, which may additionally result in poorer skin condition and more itch …”
Section: Discussionmentioning
confidence: 99%